A survey from UAV in critical areas: the advantages of technology in areas with complex terrain (GEOmedia, 2016)
The tale of two experiences in the geological and cultural heritage area throughthe use of fixed-wing drones. Innovation and high quality of the data returned from an aero-photogrammetric survey as support to the activities of the differentprofessionals. From the survey phase to the post-production all the precautions toobtain images with a very good resolution and solve obstacles for the mapping of areas not easily accessible such as quarries.